2013
DOI: 10.1089/ten.tea.2012.0733
|View full text |Cite
|
Sign up to set email alerts
|

Brain Tissue Interaction with Three-Dimensional, Honeycomb Polycaprolactone-Based Scaffolds Designed for Cranial Reconstruction Following Traumatic Brain Injury

Abstract: Following traumatic brain injury (TBI), resultant voids are unable to support injections of suspension treatments, leading to ineffective healing. Moreover, without a structure to support the large defect, the defect site suffers from mechanical instability, which may impair the healing process. Therefore, having a delivery vehicle that can temporarily fill and provide mechanical support to the defect site may alleviate the healing process. In this work, we reported for the first time, the inflammatory respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
(42 reference statements)
1
15
0
Order By: Relevance
“…Polymeric scaffolds have several advantages over metal or ceramic scaffolds. Currently used polymers, especially PCL, are slowly biodegradable, can be shaped freely with FDM technology, and are less brittle than ceramics …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Polymeric scaffolds have several advantages over metal or ceramic scaffolds. Currently used polymers, especially PCL, are slowly biodegradable, can be shaped freely with FDM technology, and are less brittle than ceramics …”
Section: Discussionmentioning
confidence: 99%
“…In literature, orientations of 60° and 45° are the most commonly used . For bone tissue engineering, scaffolds must provide sufficient initial mechanical strength and stiffness to substitute for the loss of mechanical function of the diseased, damaged, or missing tissue .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous findings [22] demonstrated that cerebral inflammation was not further aggravated in PCL and PCL/TCP groups. The attenuated expression of IL-1β was an expected outcome, as it is known from previous studies that its expression does not persist more than a few days.…”
Section: Discussionmentioning
confidence: 74%
“…[22] Apart from their potential use as biomolecule delivery vehicles, bioactive scaffolds may also be used to assist in the regeneration of the cranium [23,24], which is important for preventing neurological deterioration and significant depression after PBI. [25,26] For this purpose, we have developed PCL/tricalcium phosphate (PCL/TCP) scaffolds that are capable of promoting bone regeneration.…”
Section: Introductionmentioning
confidence: 99%